CPW‐fed Zeroth‐order Resonator Antenna Using Shorted CRLH Transmission Line. Issue 12 (23rd September 2013) - Dinesh, R.; Vinod, V. K. T.; Deepak, U.; Vinesh, P. V.; Mohanan, P.
ABSTRACT A novel composite right/left‐handed (CRLH) coplanar waveguide (CPW)‐fed zeroth‐order resonator antenna is proposed. The shorted CRLH transmission line exhibits zeroth‐order resonance at 2 GHz and operates with narrow bandwidth. The dispersion analysis is also carried out and presented in this article. The proposed antenna has been fabricated and tested. Omnidirectional radiation pattern with a gain 3.5 dBi has been obtained. © 2013 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:2844–2847, 2013